2018
DOI: 10.1002/hfm.20768
|View full text |Cite
|
Sign up to set email alerts
|

How to foster frontline employee knowledge sharing within service‐oriented enterprises: Empirical evidence from China

Abstract: Based on the context of Chinese workplace, the present research aims to explore the combined effects of proactive personality, supervisor–subordinate guanxi (s–s guanxi), and leaders’ innovation expectations on the knowledge sharing of frontline employees (FLEs). Questionnaire data from a sample of 301 FLEs within service‐oriented enterprises in China were used in this study. The results show that proactive personality and leaders’ innovation expectations are both positively related to employees’ psychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Extant studies used various mediators to explain the relationship between SMU and employees' cognition and behavior (Cai et al , 2018; Tajudeen et al , 2018; Zhang et al , 2019) and team performance (Song et al , 2019), but these effects' boundary conditions have rarely been discussed. As previous studies point out, employees' behaviors are strongly bounded by leaders and their leadership style in the context of Chinese enterprises (Zhou et al , 2019). Therefore, our research extended the theory boundary to better understand the effect of SMU on employees' spirituality.…”
Section: Conclusion and Discussionmentioning
confidence: 94%
“…Extant studies used various mediators to explain the relationship between SMU and employees' cognition and behavior (Cai et al , 2018; Tajudeen et al , 2018; Zhang et al , 2019) and team performance (Song et al , 2019), but these effects' boundary conditions have rarely been discussed. As previous studies point out, employees' behaviors are strongly bounded by leaders and their leadership style in the context of Chinese enterprises (Zhou et al , 2019). Therefore, our research extended the theory boundary to better understand the effect of SMU on employees' spirituality.…”
Section: Conclusion and Discussionmentioning
confidence: 94%
“…Studies have been conducted to analyze the role of factors such as superiorsubordinate relationships (Zhou et al, 2019), proactive personality (Hon et al, 2022), leader empowerment behaviors (Xiang et al, 2021), knowledge internalization mechanisms (Wipawayangkool & Teng, 2019), job satisfaction (Kucharska, & Erickson, 2020), and psychological ownership of knowledge (Sheshadri et al, 2021) in influencing employee knowledge sharing. Once known to others, intangible resources such as creative knowledge are challenging to confirm ownership, which causes people to prefer to protect their ownership (Brown et al, 2005), and easily triggers psychological ownership of personal knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found the influence of culture on knowledge sharing [7], [11], [13]- [15], culture on knowledge management [3], [7], [8], [16], [17] and culture collectivism for knowledge sharing [11]. However, there is no such research that links the interdependent culture which is a culture in Indonesia with a knowledge management orientation.…”
Section: Introductionmentioning
confidence: 99%